A Comparative Study of Quality of Life and Socioeconomic Status among Occupational Groups in Don Ruak Subdistrict, Nakhon Pathom Province: An Application of Sufficiency Economy Philosophy - Plubplueng, Thitima; Plubplueng, Piyapong; Laosim, Pongsawat (Ratchaphruek Journal, 2025)
The increase in informal workers during the COVID-19 pandemic reflects economic vulnerability and quality of life challenges. This research aims to compare socioeconomic status and analyze the relationship between quality of life based on the Sufficiency Economy Philosophy among occupational groups in Don Ruak Subdistrict, Nakhon Pathom Province. Data was collected through questionnaires from 325 household heads using multi-stage random sampling. Analysis methods included descriptive statistics, chi-square tests, and analysis of variance. Results showed that informal worker households had significantly lower average monthly income at 23,818.32 baht compared to formal workers and business owners, with 96.3% having below bachelor’s degree education. Regarding the quality of life, informal workers demonstrated higher levels of moderation, with 60.53% reporting no debt impact on living conditions, but showed lower economic immunity with only 61.58% having multiple income sources. While showing no significant differences in reasonableness, knowledge, and moral integrity, they exhibited significantly lower happiness levels compared to formal workers at the .05 significance level. The findings suggest the need for comprehensive support policies, particularly in systematically strengthening economic immunity and mental health care for informal workers.